The template synthesis, spectral characterizatin and thermal behaviour of new binuclear Schiff base complexes derived from N-aminopyrimidine with 2,3-butandione - Soenmez, Mehmet; Sekerci, Memet (Walter de Gruyter Gmbh, 2006)
A new series of two types of acyclic binuclear Schiff base complexes, prepared by template condensation of N-aminopyrimidine and 2,3-butandione in the presence of Cu-II, Ni-II, Co-II and Zn-II in n-BuOH solution, have been characterized by IR, elemental analyses, electronic spectral data, conductivity and magnetic measurements. From conductivity measurements, it is shown that the complex of Ni-II is electrolyte. All the complexes have sub-normal magnetic moments commensurate with their binuclear nature. The thermal behaviour of the complexes has been studied by t.g. technique.
Keywords: acyclic Schiff base complexes; template synthesis